Answer:
0
Step-by-step explanation:
because your making it all to the zero power which equals zero
Answer:
![(a+b)^n ={n \choose 0}a^{(n)}b^{(0)} + {n \choose 1}a^{(n-1)}b^{(1)} + {n \choose 2}a^{(n-2)}b^{(2)} + ..... +{n \choose n}a^{(0)}b^{(n)}](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%20%3D%7Bn%20%5Cchoose%200%7Da%5E%7B%28n%29%7Db%5E%7B%280%29%7D%20%2B%20%7Bn%20%5Cchoose%201%7Da%5E%7B%28n-1%29%7Db%5E%7B%281%29%7D%20%2B%20%7Bn%20%5Cchoose%202%7Da%5E%7B%28n-2%29%7Db%5E%7B%282%29%7D%20%2B%20.....%20%20%2B%7Bn%20%5Cchoose%20n%7Da%5E%7B%280%29%7Db%5E%7B%28n%29%7D)
Step-by-step explanation:
The Given question is INCOMPLETE as the statements are not provided.
Now, let us try and solve the given expression here:
The given expression is: ![(a +b)^n, n > 0](https://tex.z-dn.net/?f=%28a%20%2Bb%29%5En%2C%20n%20%3E%200)
Now, the BINOMIAL EXPANSION is the expansion which describes the algebraic expansion of powers of a binomial.
Here, ![(a+b)^n = \sum_{k=0}^{n}{n \choose k}a^{(n-k)}b^{(k)}](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%20%3D%20%5Csum_%7Bk%3D0%7D%5E%7Bn%7D%7Bn%20%5Cchoose%20k%7Da%5E%7B%28n-k%29%7Db%5E%7B%28k%29%7D)
or, on simplification, the terms of the expansion are:
![(a+b)^n ={n \choose 0}a^{(n)}b^{(0)} + {n \choose 1}a^{(n-1)}b^{(1)} + {n \choose 2}a^{(n-2)}b^{(2)} + ..... +{n \choose n}a^{(0)}b^{(n)}](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%20%3D%7Bn%20%5Cchoose%200%7Da%5E%7B%28n%29%7Db%5E%7B%280%29%7D%20%2B%20%7Bn%20%5Cchoose%201%7Da%5E%7B%28n-1%29%7Db%5E%7B%281%29%7D%20%2B%20%7Bn%20%5Cchoose%202%7Da%5E%7B%28n-2%29%7Db%5E%7B%282%29%7D%20%2B%20.....%20%20%2B%7Bn%20%5Cchoose%20n%7Da%5E%7B%280%29%7Db%5E%7B%28n%29%7D)
The above statement holds for each n > 0
Hence, the complete expansion for the given expression is given as above.
Answer: 54 square feet
Step-by-step explanation:
To find perimeter of a rectangle we must use the formula l+l+w+w=p where l and w represent width and length
Since we know length and width is x=12 just substitute so
15+15+12+12=54 so 54 is the perimeter
Answer:
The equation is: y = 1/2x + 7
Step-by-step explanation:
The slope of j is -2. The slope of a line perpendicular to line j has a negative inverse: 1/2. The point is (-8, 3).
Use the point slope form of the equation:
y - y1 = m(x - x1)
Substitute:
y - 3 = 1/2(x - (-8))
y - 3 = 1/2x + 4
y = 1/2x + 4 + 3
y = 1/2x + 7
Proof:
Solve for f(x) when x = -8.
f(x) = 1/2x + 7
f(-8) = 1/2(-8) + 7
= -8/2 + 7
= -4 + 7
= 3, giving the point (-8, 3)
Answer:
.3%, 21/7000=.003
Step-by-step explanation:
to make it by percent you multipy by 100